2016
DOI: 10.1136/heartjnl-2015-308891
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid approach improves success of chronic total occlusion angioplasty

Abstract: Hybrid-trained operators can achieve overall success rates of 90% in real world practice with acceptable MACE. Use of dissection re-entry and investment procedures maintains high success rates in complex lesions. The hybrid approach represents a significant advance in CTO treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 22 publications
3
110
0
6
Order By: Relevance
“…In recent years, several large multicenter registries have reported higher success (≈85%–90%) with acceptable complication rates in CTO PCI at various experienced centers and with operators from all around the world, although less optimal results have been reported from all‐comer PCI registries (Table 2). 8, 25, 26, 27, 28, 29, 30, 31, 32 …”
Section: Success Of Cto Pcimentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several large multicenter registries have reported higher success (≈85%–90%) with acceptable complication rates in CTO PCI at various experienced centers and with operators from all around the world, although less optimal results have been reported from all‐comer PCI registries (Table 2). 8, 25, 26, 27, 28, 29, 30, 31, 32 …”
Section: Success Of Cto Pcimentioning
confidence: 99%
“…AWE (ie, sequential use of various guidewires in the antegrade direction, from the proximal to the distal part of the vessel) is the most commonly used initial and final CTO crossing technique (66%–78%),25, 26, 27, 28 especially for less complex occlusions 62…”
Section: Radiationmentioning
confidence: 99%
“…Significant improvements, however, have been achieved in recent years resulting in high success rates by several expert operators and centers. 7,8 The goal of the present review is to provide an update on the current status and future directions of CTO-PCI.…”
Section: N Introductionmentioning
confidence: 99%
“…In a report from the Prospective Global Registry for the Study of Chronic Total Occlusion Intervention (PROGRESS-CTO), Christopoulos et al 7 reported 91% technical success and a 1.7% rate of major adverse cardiac events among 1,036 consecutive CTOPCIs performed using the hybrid approach between 2012 and 2015 at 11 US centers. 7 Wilson et al 8 Less favorable outcomes, however, have been observed at less experienced centers. In an analysis of 594,510 PCI cases performed between 2009 and 2013 in patients with stable coronary artery disease in the National Cardiovascular Data Registry (NCDR), CTO-PCI represented 3.8% of the total PCI volume and was associated with significantly lower procedural success (59% versus 96%, P , .001) and higher risk for complications (1.6% versus 0.8%; P , .001) compared with non-CTO-PCI.…”
mentioning
confidence: 99%
See 1 more Smart Citation